Effect of maternal supplementation in dry season on growth development of Nellore calves - Rodrigues, Liziana Maria (2018)
The objective of the present study was to evaluate the effect of maternal nutrition on cow performance as well as progeny growth by gene expression in muscle and intestine from birth until weaning. Nine-two pregnant cows were raised on Brachiaria brizantha pasture (8.2% CP and 68.5% NDF) and supplemented with mineral (NS) or a protein supplement (SUPP) (36%CP, 0.2%BW) from middle of gestation until calving. During gestation, cows were weighted and had BCS measured monthly. Cows entered in a FTAI protocol 60 days after calving and had the pregnancy rate measured. At calving, calves were weighed, identified and six calves from each treatment were slaughtered. Body components were measured and samples of muscle and jejunum were collected for histological and gene expression analyses. In addition, 10 calves from each treatment had muscle biopsy samples collected at 11 ± 4 days and at 240± 4. Calves were weighed again at 120 days after birth and at weaning. Least square means of all data were analyzed using the GLM procedure of SAS. Cow BW and BCS did not differ during the study (P > 0.05), however, SUPP cows gained more BW (79.2kg vs. 95.3kg, P = 0.03) and body condition (0.01 vs. 0.36 units, P = 0.05) during gestation. As a result, pregnancy rate in the subsequent breeding season tended (62.1% vs. 78.6%, P = 0.10) to be greater for SUPP cows. On the other hand, BW gain during lactation was greater for cows from the NS group (59.1kg vs. 26.4kg, P = 0.05). Calves from SUPP cows had greater birth BW compared to NS calves (33.7kg vs. 35.8kg, P = 0.05). However no differences in BW at weaning or ADG of calves were found. Body components from slaughtered calves did not differ between treatments (P > 0.05), except for smaller intestine length that were greater for NS calves (17.2m vs. 15.9m, P = 0.05) with small crypt size (13.1µm vs. 19.5µm P < 0.01). Twenty-four hours after birth muscle of calves from SUPP group had greater expression of WNT10B (P = 0.01), PPARG (P = 0.03), CD36 (P = 0.04) and TGFβ1 (P = 0.01) compared to calves from NS cows with no differences in the other genes. This greater expression of WNT10B, PPARG, CD36 and TGFβ1 indicates that 24 hours after birth, calves from SUPP group still had multipotent cells performing differentiation for myogenesis, adipogenesis and fibrogenesis. Muscle of SUPP calves had less expression of C/EBPA (P = 0.01) and FABP4 (P = 0.07) than calves from NS cows 11 days after birth, suggesting greater amount of adipocytes resulting from an early adipogenesis in the NS calves as a metabolic adaptation to increase the body reserves. At weaning, muscle of SUPP calves had a tendency to have greater expression of PPARG (P= 0.08), and greater ZFP423 (P = 0.04) and TGFβ1 (P = 0.02) than muscle of NS calves. The increase in expression of adipogenic genes in SUPP calves supports the hypothesis that these animals had a late adipogenesis. β-catenin, mTOR COL3A1 and FN1 genes were not affected by maternal diet (P > 0.05). In conclusion, supplementation of pregnant cows during dry season leads to a positive effects for subsequent breeding season and offspring birth weight. Supplementation had greater effects on myogenesis, and adipogenesis of calves. While calves born from restricted cows presented some gut adaptations for restricted condition.